Penerapan Model Pembelajaran Kooperatif Tipe NHT Materi Pokok Kalor Kelas VII SMPK ST. Familia - Lipikuni, Hilary Fridolin; Dude, John Mikael (Jurnal Penelitian Pendidikan Fisika, 2021)
The purpose of this study is to describe the ability of teachers in managing learning activities, to describe the completeness of indicators of student learning outcomes, to describe the completeness of student learning outcomes, to describe the responses of students to the learning process, to describe the cooperative skills of students by applying the cooperative learning model type Numbered Heads Together. This type of research is descriptive with research subjects are teachers and students of class VII SMPK St. Kupang Familia, amounting to 25 people. The research data collection techniques were observation, tests, and questionnaires. While the instrument used was the learning management observation sheet which included planning assessment sheets, implementation observation sheets, and learning evaluation assessment sheets, student cooperative skills observation sheets, learning outcomes test, and student response questionnaires. The data analysis technique of this research is descriptive analysis. The results of the descriptive analysis show that the application of the Numbered Heads Together cooperative learning model is the subject matter of the heat for class VII SMPK St. Familia Kupang in the odd semester of the 2017/2018 school year is optimal.